PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN NUMERASI MURID FASE F PADA MATERI SISTEM RESPIRASI DI SMAS ADABIAH 2 PADANG - Fitri, Annisa; Syamsurizal; Zulyusri; Hijrah Selaras, Ganda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of implementing the Problem Based Learning (PBL) model on the numeracy skills of Phase F students in the respiratory system unit at SMAS Adabiah 2 Padang. This study employed a quantitative approach using a quasi-experimental method and a Posttest-Only Control Group design. The study population consisted of all 180 students in Grade 11 Phase F. The research sample was selected using purposive sampling, specifically Class XI F2 as the experimental class and Class XI F5 as the control class, each consisting of 36 students. The experimental class received instruction using the Problem Based Learning model, while the control class received the standard instruction typically taught by the teacher on the respiratory system topic. The research instrument consisted of a numeracy skills test comprising 30 multiple-choice questions that had been validated. Data analysis was conducted using normality tests, homogeneity tests, and an Independent Samples T-Test hypothesis test with the assistance of SPSS Statistics 25. The results of the study showed that the average numeracy ability of the experimental class was 86.48%, while that of the control class was 78.24%. The results of the hypothesis test showed a significance value of 0.000 (<0.05), so it can be concluded that the Problem Based Learning model has a positive and significant effect on students’ numeracy skills.